An Evaluation of Protected Area Policies in the European Union - Tristan Earle Grupp; Prakash Mishra; Mathias Reynaert; Arthur A. van Benthem (Center for Economic Studies and ifo Institute (CESifo), 2023)
The European Union designates 26% of its landmass as a protected area, limiting economic development to favor biodiversity. This paper uses the staggered introduction of protected-area policies between 1985 and 2020 to study the selection of land for protection and the causal effect of protection on vegetation cover and nightlights. Our results reveal protection did not affect the outcomes in any meaningful way across four decades, all countries, protection cohorts, and a wide range of land and climate attributes. We conclude that European conservation efforts lack ambition because policymakers select land for protection not threatened by development.
Keywords: Q23; Q24; Q57; R14; 330; land protection; conservation; biodiversity; deforestation; vegetation cover; nightlights; staggered difference-in-differences